2020
DOI: 10.1177/1521025120944828
|View full text |Cite
|
Sign up to set email alerts
|

Fostering a Sense of Belonging Using a Multicontext Approach

Abstract: This review of research discusses how applications of multicontext theory can help foster a sense of belonging for students in higher education, resulting in stronger persistence. Multicontext theory may offer an approach to designing learning experiences and environments that take into account varied ways of thinking and knowing, are relevant inside and outside of the classroom, and can both enrich and encompass the lives of students on and off campus. Focusing on faculty-student interactions is one area with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Lastly, the differential relationships between family academic discussions and GPA merits further research with a larger sample of diverse students. Cultural dissonance between home and postsecondary contexts may explain this finding (Moore, 2020). For Latinx and Black students, interventions targeted at enhancing academic discussions with family, peers and college personnel may prove successful in reducing student departure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the differential relationships between family academic discussions and GPA merits further research with a larger sample of diverse students. Cultural dissonance between home and postsecondary contexts may explain this finding (Moore, 2020). For Latinx and Black students, interventions targeted at enhancing academic discussions with family, peers and college personnel may prove successful in reducing student departure.…”
Section: Discussionmentioning
confidence: 99%
“…We were surprised to observe a negative relationship between family academic discussions and academic self-efficacy for Latinx students. Considered in tandem with the negative family academic discussions relationship with GPA for both Black and Latinx students it is possible a mismatch between family discussion topics and postsecondary academic demands exists (Moore, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that high levels in the sense of belonging in university students contributes to increasing their levels of participation, being able to seek help in the face of difficulties, feeling less alone, anxious or depressed, increasing the use of self-regulation strategies and raises levels of academic self-confidence and motivation [64,66,77]. In addition, various investigations have observed that the sense of belonging turns out to be a direct predictor of study engagement, dropout, and permanence in studies [40,41,45,65,66,73,[77][78][79][80].…”
Section: Sence Of Belongingmentioning
confidence: 99%
“…However, this work has been limited, and we are not aware of any studies that have directly examined the impact of office hours on student learning or academic performance in STEM. Similarly, while past work has suggested that attendance at office hours may positively impact student affect like sense of belonging and can help build the instructor–student relationship ( Moore, 2020 ; Guzzardo et al. , 2021 ), there have not been any empirical studies that measure the impact of office hours on student affect.…”
Section: Introductionmentioning
confidence: 99%